METHODOLOGICAL ANALYSIS OF DEFINITIONS OF CONCEPTS “COMPETENCY” AND “LEARNING OUTCOMES” - A. M. Shekhmirzova (Science and Innovation Center Publishing House, 2020)
The article provides a methodological analysis of the definitions of the concepts of «competence» and «learning outcomes». The essential characteristic of the concepts under consideration in the context of the requirements of the new standards is given. The importance of the structural components of the educational program in the acquisition of competencies is emphasized. The understanding of definitions is compared with the approach in the Tuning project.